Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 5 - Exponential Functions - 5.2 Solving Equations Using Exponent Rules - 5.2 Exercises: 58

Answer

$t = 2$

Work Step by Step

$12(6^{t}) = -252 + 19(6^{t})$ $12(6^{t}) - 19(6^{t}) = -252$ $(12 - 19)(6^{t}) = -252$ $-7(6^{t}) = -252$ $6^{t} = 36$ $6^{t} = 6^{2}$ $t = 2$ Check: $ 12(6^{t}) - 19(6^{t})$ $= 12(6^{2}) - 19(6^{2})$ $= 12(36) - 19(36)$ $= 432 - 684$ $= -252$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.